2015
DOI: 10.1002/ece3.1646
|View full text |Cite
|
Sign up to set email alerts
|

Warming decreased and grazing increased plant uptake of amino acids in an alpine meadow

Abstract: Organic nitrogen (N) uptake by plants has been recognized as a significant component of terrestrial N cycle. Several studies indicated that plants have the ability to switch their preference between inorganic and organic forms of N in diverse environments; however, research on plant community response in organic nitrogen uptake to warming and grazing is scarce. Here, we demonstrated that organic N uptake by an alpine plant community decreased under warming with 13C–15N‐enriched glycine addition method. After 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…The average coverages of graminoids, forbs, and legumes were about 86%, 86%, and 28%, respectively (Wang et al, 2012). A detailed description of the experimental site can be found in our previous studies Ma et al, 2015).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The average coverages of graminoids, forbs, and legumes were about 86%, 86%, and 28%, respectively (Wang et al, 2012). A detailed description of the experimental site can be found in our previous studies Ma et al, 2015).…”
Section: Study Sitementioning
confidence: 99%
“…Soil pH was determined using a pH meter in a 1:5 soil-water suspension. The soil microbial biomass was measured with the chloroform fumigation-extraction method, as detailed in our previous report (Ma et al, 2015).…”
Section: Soil Sampling and The Measurements Of Soil Properties And Bementioning
confidence: 99%
“…High‐elevation systems differ from those located at high latitudes in light, temperature and precipitation patterns, all of which can influence N cycling, and therefore responses of N dynamics to warming in alpine areas remain largely unknown (but see Ma et al . ; Dawes et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The current understanding of how N dynamics in cold ecosystems will respond to increasing temperatures is almost entirely based on studies in (sub)arctic regions. High-elevation systems differ from those located at high latitudes in light, temperature and precipitation patterns, all of which can influence N cycling, and therefore responses of N dynamics to warming in alpine areas remain largely unknown (but see Ma et al 2015;Dawes et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated temperature can promote soil nitrification and net N mineralization rate ( Melillo et al., 2011 ), but decrease the soil available P content ( Dijkstra et al., 2012 ), leading to the positive effect on plant nutrient uptake, higher plant N:P ratio, and lower C:N and C:P ratios. Conversely, drought induced by warming can depress N and P uptake by plant ( Ma et al., 2015 ), decreasing N and P concentration in plant tissues, and ultimately leading to a lower C:N and C:P ratios in plant ( Viciedo et al., 2019 ). Previous studies have reported inconsistent results about the response of soil and plant stoichiometry to warming in QTP.…”
Section: Introductionmentioning
confidence: 99%